Optimalisasi Biaya dan Waktu dalam Manajemen Proyek: Studi Kasus Sistem Manajemen Gudang Digital Berbasis QR Code - Zarafat Risian Rafli; Kusuma, Mochamad Iqbal Hadi Jaya; Muafa, Muhammad Mahdi; Ocktaviani, Dina Ayu; Aini , Zahra Qudratul (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to analyze cost and time optimization in project management through a case study of developing a QR Code–based Digital Warehouse Management System. The project was carried out by a team of students from the Logistics Management Study Program as a practical implementation of modern project management concepts in an academic environment. The research employed a descriptive qualitative case study approach, including observation, documentation, and literature analysis. The results indicate that the use of QR Code technology significantly improves time efficiency in stock recording by up to 80% and reduces the risk of human error. In terms of cost, the project successfully optimized resources by utilizing personal devices and open-source software, eliminating the need for additional infrastructure investment. The project also demonstrated effective implementation of the Work Breakdown Structure (WBS), risk management, and evaluation based on the Triple Constraint principle. These findings highlight that simple digital innovations can greatly enhance operational efficiency and project management performance, making them a strategic solution for SMEs in the digitalization of warehouse operations.